The crimean crisis in the context of new Russian geopolitics - (:unkn) unknown (SETA, 2014)
Over the past months, the crisis in Crimea presented the world with a case study on how rapidly national borders may shift in the 21st century. The turmoil in Ukraine began in November 2013 as widespread protests erupted following a last-minute decision by former president Viktor Yanukovych's to suspend talks on a trade pact with the European Union under pressure from the Russian government. The pro-Russian leadership in Crimea organized an impromptu referendum where the vast majority of participants voted in favor of uniting with the Russian Federation. This article provides an analysis of recent developments in Crimea in the context of Russian policy in the region.